Energy Management System for Solar-powered Streetlighting Systems - Tounsi Fokui Willy Stephen; Wandji Danube (E3S Web of Conferences, 2022)
Public lighting or street lighting systems are raised sources of light on the edge of the road or walkway, that is turned ON at night or during bad weather to lighten the streets and turned OFF in the morning. The major problem with streetlights is their excessive energy consumption as most of that energy is wasted because the streets are empty between about 11 pm to 5 am. This also leads to the rapid degration of the streetlights and increased cost of maintenance operations which constitute a financial burden to the municipality. This paper solves this problem by proposing an energy management system for solar-powered streetlights that in addition to turning the streetlights ON when places are dark, puts the streetlights in an energy-saving mode when there is no one on the streets. Vibration sensors are used as motion detectors. The study is focused on the second bridge on the River Wouri, Douala, Cameroon. Simulation of the work is done using Proteus Professional and the results obtained are compared with an estimated daily energy consumption of the existing streetlights on the bridge. It is seen that the energy consumption of the proposed system is 25740Wh, and this is far lesser compared to 187200Wh consumed by the existing system assuming each lamp is 150W.